The International Civil Responsibility for Terrorism Financing - Rajab Salman , Researcher. Walid (Basra studies journal, 2025)
The harm resulting from terrorist financing arises immediately upon the commission of the financing act itself. In conclusion, it may be affirmed that the concept of international responsibility for terrorist financing is established when a state fails to comply with its international treaty obligations concerning the suppression and prevention of terrorist acts and their financing. Such a breach engages the state’s responsibility and exposes it to international sanctions that may be imposed by other states. Furthermore, it obliges the violating state to provide appropriate compensation to other states or to their nationals whenever harm results from its negligence or failure to implement its obligations. In addition to treaty-based commitments, there are also general obligations and principles of international law which require states to respect the independence, sovereignty, and stability of other states. This implies that even in the absence of a specific provision explicitly criminalizing the financing of terrorism, states remain under a duty to suppress and combat terrorist financing in all its forms and manifestations. International responsibility for terrorist acts may arise directly, when such acts are carried out in the name of the state or on its behalf, or indirectly, as a result of its negligence, failure, or collusion in fulfilling its international obligations. In either case, the state is bound to make full reparation for all damages and consequences that flow from such acts.